2002
DOI: 10.1093/emboj/cdf498
|View full text |Cite
|
Sign up to set email alerts
|

RPD3 is required for the inactivation of yeast ribosomal DNA genes in stationary phase

Abstract: rRNA transcription in Saccharomyces cerevisiae is performed by RNA polymerase I and regulated by changes in growth conditions. During log phase,~50% of the ribosomal DNA (rDNA) genes in each cell are transcribed and maintained in an open, psoralenaccessible conformation. During stationary phase, the percentage of open rDNA genes is greatly reduced. In this study we found that the Rpd3 histone deacetylase was required to inactivate (close) individual rDNA genes as cells entered stationary phase. Even though 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
124
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 58 publications
11
124
1
Order By: Relevance
“…Human cells contain about 400 ribosomal genes in tandem repeats at nucleolus organizer regions encoded on five pairs of chromosomes 13, 14, 15, 21, and 22. Previous studies have indicated that only 30 -50% of rRNA genes display an open accessible chromatin structure (3,4).…”
Section: Transcriptional Function and Expression Profile Of Mcrs1 In Thementioning
confidence: 99%
See 1 more Smart Citation
“…Human cells contain about 400 ribosomal genes in tandem repeats at nucleolus organizer regions encoded on five pairs of chromosomes 13, 14, 15, 21, and 22. Previous studies have indicated that only 30 -50% of rRNA genes display an open accessible chromatin structure (3,4).…”
Section: Transcriptional Function and Expression Profile Of Mcrs1 In Thementioning
confidence: 99%
“…Human diploid cells contain about 400 ribosomal genes organized as tandem repeats at nucleolus organizer regions encoded on chromosomes 13, 14, 15, 21, and 22 (1,2). rRNA gene transcription varies according to the demand for ribosome production and protein synthesis, and in yeast and murine cells, only 30 -50% of the rRNA genes are in an open structure that facilitates active transcription (3,4). Transcription of rRNA is extensively regulated by a large number of proteins such as growth factors, CBP (cAMPresponse element-binding protein (CREB)-binding protein), Rb, p53, and Myc (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…At the HM loci and telomeres, hypoacetylated H3 and H4 promote the interaction of Sir3 and Sir4 with nucleosomes, thereby facilitating the formation and spread of silent chromatin (Braunstein et al, 1993(Braunstein et al, , 1996Hecht et al, 1995;Wu and Grunstein, 2000;Carmen et al, 2002;Liou et al, 2005). Hypoacetylated histones are present at the rDNA (Bryk et al, 2002;Buck et al, 2002;Sandmeier et al, 2002;Huang and Moazed, 2003), although how they contribute to rDNA silencing remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…At the HM loci and telomeres, hypoacetylated H3 and H4 promote the interaction of Sir3 and Sir4 with nucleosomes, thereby facilitating the formation and spread of silent chromatin (Braunstein et al, 1993(Braunstein et al, , 1996Hecht et al, 1995;Wu and Grunstein, 2000;Carmen et al, 2002;Liou et al, 2005). Hypoacetylated histones are present at the rDNA (Bryk et al, 2002;Buck et al, 2002;Sandmeier et al, 2002;Huang and Moazed, 2003), although how they contribute to rDNA silencing remains unclear.Cells lacking K4-methylated histone H3 exhibit defects in transcriptional silencing at the rDNA and telomeres (Nislow et al, 1997;Briggs et al, 2001;Bryk et al, 2002;Nagy et al, 2002;Mueller et al, 2006). Set1 is the catalytic subunit of the COMPASS complex that is required for mono-, di-, and trimethylation of histone H3 on K4.…”
mentioning
confidence: 99%
“…1A), accounting for ;50% of all rRNA genes, is silenced via epigenetic mechanisms that include changes in DNA methylation and histone modification (Earley et al 2006(Earley et al , 2010Pontvianne et al 2010Pontvianne et al , 2012. Chromatin modifications mediate rRNA gene dosage control in yeast, mouse, and human cells as well (Sandmeier et al 2002;McStay and Grummt 2008;Grummt and Langst 2013).…”
mentioning
confidence: 99%